2020
DOI: 10.1182/bloodadvances.2020002173
|View full text |Cite
|
Sign up to set email alerts
|

Safety of a strategy combining D-dimer testing and whole-leg ultrasonography to rule out deep vein thrombosis

Abstract: Guidelines for the diagnostic workup of deep vein thrombosis (DVT) recommend assessing the clinical pretest probability before proceeding to D-dimer testing and/or compression ultrasonography (CUS) if the patient has high pretest probability or positive D-dimer. Referring only patients with positive D-dimer for whole-leg CUS irrespective of pretest probability may simplify the workup of DVT. In this prospective management outcome study, we assessed the safety of such a strategy. We included consecutive outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[ 37 , 38 ] It is one of the markers that respond to a hypercoagulable state and secondary hyperfibrinolysis in vivo , as its elevation reflects enhanced secondary fibrinolytic activity and excessive thrombin production. [ 39 , 40 ] Myocardial infarction, venous thrombosis or PE, diffuse intravascular coagulation can all lead to increased D-Di. [ 41 ] Elevated D-Di after laparoscopic hepatic haemangioma resection reminds hyperfibrinolytic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 37 , 38 ] It is one of the markers that respond to a hypercoagulable state and secondary hyperfibrinolysis in vivo , as its elevation reflects enhanced secondary fibrinolytic activity and excessive thrombin production. [ 39 , 40 ] Myocardial infarction, venous thrombosis or PE, diffuse intravascular coagulation can all lead to increased D-Di. [ 41 ] Elevated D-Di after laparoscopic hepatic haemangioma resection reminds hyperfibrinolytic hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The highly selected population in the evaluation had a 27% rule-in rate for DVT and/or PE, meaning that this was not a typical emergency medicine screening population. Research on other emergency medicine populations has identified a variable prevalence of VTE but generally much lower, ranging from 7.4% to 20% 10–12. Patients were identified by finding those that had obtained imaging.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of CUS without considering the clinical context (a sign of thrombosis) is limited [54,56]. It should be interpreted by including C-PTP and/or calf swelling with a diameter ≥ 3 cm greater than that of the asymptomatic calf [53,57]. The more sensitive method is magnetic resonance venography (sensitivity 92%, specificity 99%) and should be performed as the next diagnostic step if an isolated deep vein thrombosis in the pelvis is suspected but cannot be safely ruled out using ultrasonography due to the low sensitivity of 50% (the specificity was 99%) [58].…”
Section: Diagnostic Value Of Bilateral Venous Compression Ultrasound ...mentioning
confidence: 99%